Geographic variation of Sebastes mentella in the Northeast Arctic derived from a morphometric approach - Saborido-Rey, Fran; Nedreaas, Kjell (ICES Journal of Marine Science, 2000)
11 pages, 9 figures, 5 tables. At present there is considered to be only one management unit of Sebastes mentella in the Northeast Arctic. A morphometric analysis was conducted to compare specimens from different locations and different times of the year. Residuals of the regression between each morphometric variable and standard length were used as input in a stepwise discriminant analysis, which revealed morphometric differences between three main regions: Svalbard, the Barents Sea and the Norwegian Sea, with the Lofoten area being an intermediate area where fish from the other three areas are present during some of the year. A previously described spawning migration pattern can also be derived from this analysis; the implications on survey design in this region are discussed. This study was supported by the European Union (ERBFMBICT 960772). Peer reviewed